2023
DOI: 10.3390/molecules28093714
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oil Composition and Antioxidant Activity of Oregano and Marjoram as Affected by Different Light-Emitting Diodes

Abstract: Oregano and marjoram are important aromatic spices in the food industry, as well as medicinal plants with remarkable antioxidant properties. Despite their popularity, little is known about treatments that would influence the antioxidant capacity of essential oils. In this study, different spectra of LED light, namely blue, red, white, blue-red, and natural ambient light as a control, were applied to assess the essential oil content, composition, flavonoid, phenolic, and antioxidant capacity of oregano and marj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 41 publications
1
0
0
Order By: Relevance
“…Since ajowan seeds were used in the present study for essential oil analysis, the discrepancies observed between the results obtained for thyme and ajowan could be explained with regard to the organs in which the oils accumulated. This explanation is confirmed by the results reported elsewhere that highlighted changes in monoterpene frequencies are based on phenological differences and harvested organs [ 4 , 48 ]. Finally, the positive correlations between the precursors and final products might be attributed to the complete transformation of the precursors.…”
Section: Resultssupporting
confidence: 88%
“…Since ajowan seeds were used in the present study for essential oil analysis, the discrepancies observed between the results obtained for thyme and ajowan could be explained with regard to the organs in which the oils accumulated. This explanation is confirmed by the results reported elsewhere that highlighted changes in monoterpene frequencies are based on phenological differences and harvested organs [ 4 , 48 ]. Finally, the positive correlations between the precursors and final products might be attributed to the complete transformation of the precursors.…”
Section: Resultssupporting
confidence: 88%